The Role of Sarak Opat in Preventing Prostitution: An Islamic Criminal Law Perspective - Ahyar Gayo; Azhari Yahya; Diana Yusyanti; Evi Djuniarti; Muhammad Habibi MZ (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2026)
Prostitution in Central Aceh, despite the implementation of Qanun Jinayat as Islamic criminal law, reflects ongoing challenges in the effectiveness of Islamic law enforcement within local communities. This study examines the role of Sarak Opat, a traditional customary institution in Aceh, in preventing prostitution and strengthening the enforcement of Islamic criminal law. Using an empirical legal research method with a case-study approach in Central Aceh, data were collected through field observations, structured interviews with Sarak Opat members, community leaders, and law enforcement officers, as well as literature analysis. The study finds that Sarak Opat plays a significant role in preventing prostitution through strengthening the â€œGolden Triangleâ€ relationship among customary leaders, government authorities, and religious leaders; conducting moral and religious socialization; providing public education regarding the dangers of moral deviance; supervising lodging businesses; and supporting the enforcement of sanctions against proven violations. The findings demonstrate that the revitalization of customary institutions contributes positively to the implementation of Islamic criminal law while simultaneously reinforcing social order and local wisdom values. This study contributes to the development of Islamic legal scholarship by offering an integrative model among adat law, Islamic law, and national law in addressing moral crimes within Indonesiaâ€™s plural legal system.